Magnetic abrasive material with core-shell structure and preparation method of magnetic abrasive material

By adopting core-shell structure magnetic abrasives, using the hard phase distribution in the ferromagnetic core and the cladding layer, the problems of high cost, poor performance and short life in the existing magnetic abrasive preparation technology are solved, and higher magnetic permeability and longer service life are achieved.

CN119709125AActive Publication Date: 2025-03-28LANZHOU UNIVERSITY OF TECHNOLOGY

Patent Information

Application Number
CN202411919306.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-03-28
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

The existing magnetic abrasive preparation technology has problems such as high cost, poor performance and short life, and the morphology and particle size are uncontrollable, and the hard phase distribution is unreasonable, which affects the processing quality.

Method used

The magnetic abrasive is adopted for core-shell structure, including a ferromagnetic core and a shell covered on its surface. The shell consists of a transition bonding layer and a hard phase embedded on its surface. The hard phase is uniformly distributed through ball milling and sintering processes and is closely connected to the ferromagnetic.

Benefits of technology

The regular morphology and uniform hard phase distribution of magnetic abrasives are achieved, which significantly improves the magnetic properties and service life of magnetic abrasives and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709125A_ABST
    Figure CN119709125A_ABST
Patent Text Reader

Abstract

The invention provides a core-shell structure magnetic abrasive and a preparation method thereof, and belongs to the technical field of magnetic abrasive preparation. According to the core-shell structure magnetic abrasive provided by the invention, through the arrangement of the core-shell structure, the magnetic abrasive has regular morphology and size, and irregular morphology and uncontrollable particle size caused by later processing are avoided; the transition bonding layer is arranged on the surface of the ferromagnet core, so that the hard phase is uniformly distributed on the surface of the ferromagnet, and the problem of uneven distribution of the hard phase is avoided; the transition bonding layer is connected with the hard phase through metallurgical bonding, the ferromagnet and the hard phase are tightly connected together, a magnetic channel is established through the formed intermetallic compound interface diffusion layer, the magnetic dilution effect of the hard phase is weakened, and the magnetic performance of the magnetic abrasive is remarkably enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of magnetic abrasive preparation, and in particular relates to a core-shell structure magnetic abrasive and a preparation method thereof. Background Art

[0002] Magnetic grinding is a method of grinding the processed surface by placing magnetic abrasives into a magnetic field so that the abrasives are arranged along the magnetic lines of force under the action of the magnetic field to form a magnetic brush. This magnetic brush has excellent polishing performance and good plasticity. It has good adaptability to various processed surfaces, has a small temperature rise and good self-sharpening properties under the rolling of the abrasive. Therefore, it has good advantages over traditional surface processing and has attracted widespread attention at home and abroad.

[0003] Magnetic abrasives, as grinding tools for magnetic grinding and finishing, are the core of magnetic grinding technology and play a key role in this processing method. The basic components of magnetic abrasives are divided into two parts, a magnetic conductive phase matrix and a hard grinding phase. The role of the magnetic conductive phase matrix is ​​to enable the abrasive to produce sufficient grinding pressure on the workpiece surface under the action of the magnetic field, while the role of the hard grinding phase is to produce grinding micro-cutting. The technical difficulty lies in the fact that magnetic abrasives must meet the following requirements at the same time: having appropriate strength, hardness, toughness and stable physical and chemical properties; taking into account both magnetic permeability and grinding efficiency; and having strong soft magnetic properties, that is, easy to magnetize and demagnetize for easy replacement of abrasives.

[0004] However, so far, the preparation technology of magnetic abrasives is very imperfect, resulting in high cost, poor performance, short life and inability to industrialize production. Domestically, magnetic abrasives are mainly prepared by sintering, bonding, chemical composite plating and sol-gel methods. Among them, the morphology and particle size of abrasives prepared by sintering and bonding methods are uncontrollable, the hard phase distribution is unreasonable, and there are a large number of cracks in the abrasives, which ultimately affect the processing quality of the abrasives; the abrasives prepared by chemical composite plating and sol-gel methods have poor bonding between the two, and the hard phase is not magnetic, which will reduce the magnetic properties of the magnetic abrasives. Summary of the invention

[0005] The purpose of the present invention is to provide a core-shell structure magnetic abrasive and a preparation method thereof. The magnetic abrasive provided by the present invention has a regular morphology, a uniform distribution of hard phases, a firm combination of ferromagnetic and hard phases, excellent magnetic properties, and good use effects.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The invention provides a core-shell structured magnetic abrasive, comprising a ferromagnetic core and a shell coated on the surface of the ferromagnetic core; the shell comprises a transition bonding layer and a hard phase embedded on the surface of the transition bonding layer, and the transition bonding layer comprises a coating layer formed by nano iron powder and an interface diffusion layer between interfaces.

[0008] Preferably, the ferromagnetic core comprises one or more of pure Fe, FeSi or FeNi.

[0009] Preferably, the hard phase comprises corundum or silicon carbide.

[0010] Preferably, the interface diffusion layer includes a Fe—Si or Fe—Al layer.

[0011] The present invention also provides a method for preparing the core-shell structure magnetic abrasive described in the above technical solution, comprising the following steps:

[0012] 1) mixing nano iron powder and ferromagnetic material and then performing a first ball milling to obtain a first composite powder; the mass content of the nano iron powder in the first composite powder is 15-25%;

[0013] 2) subjecting the first composite powder obtained in step 1) to a second ball milling with a hard phase to obtain a second composite powder, and sintering the second composite powder to obtain a magnetic abrasive; the mass content of the hard phase in the second composite powder is 15-30%; the sintering is carried out in an inert atmosphere at a sintering temperature of 800-1200°C.

[0014] Preferably, in step 1), the particle size of the ferromagnetic material is 50-80 μm, and the particle size of the nano iron powder is 30-80 nm.

[0015] Preferably, the ball-to-material ratio of the first ball milling in step 1) is (10-15):1, the rotation speed is 150-250 rpm, and the ball milling time is 6-8 hours.

[0016] Preferably, in step 2), the particle size of the hard phase is 5 to 20 μm.

[0017] Preferably, the ball-to-material ratio of the second ball milling in step 2) is (10-15):1, the rotation speed is 150-250 rpm, and the ball milling time is 6-8 hours.

[0018] Preferably, the heating rate of sintering in step 2) is 30-50° C. / min.

[0019] The core-shell structure magnetic abrasive provided by the present invention comprises a ferromagnetic core and a shell coated on the surface of the ferromagnetic core; the shell comprises a transition bonding layer and a hard phase embedded on the surface of the transition bonding layer, and the transition bonding layer comprises a coating layer formed by nano iron powder and an interface diffusion layer between interfaces. The present invention provides the magnetic abrasive with a regular morphology and size through the setting of the core-shell structure, avoiding the irregular morphology and uncontrollable particle size caused by later processing; by setting the transition bonding layer on the surface of the ferromagnetic core, the hard phase is evenly distributed on the surface of the ferromagnet, avoiding the problem of uneven distribution of the hard phase; the transition bonding layer and the hard phase are connected by metallurgical bonding, not only the ferromagnet and the hard phase are tightly connected together, but also the intermetallic compound interface diffusion layer formed, establishes a magnetic channel, weakens the magnetic dilution effect of the hard phase, and significantly enhances the magnetic properties of the magnetic abrasive. The results of the embodiments show that the magnetic abrasive provided by the present invention is spherical, has a uniform distribution of hard phases, and has higher magnetic permeability and lower coercive force than traditional magnetic abrasives. The magnetic abrasive provided by the present invention is used to process a 10 mm zirconium alloy tube wall with an initial roughness Ra = 0.317 ± 0.01 μm for 10 min, and the roughness Ra = 0.185 ± 0.01 μm, and the grinding life is increased to 80 min. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is a schematic diagram of the process of preparing magnetic abrasive in Example 1 of the present invention;

[0021] Figure 2 This is a microscopic morphology image of the magnetic abrasive prepared in Example 1 of the present invention magnified 2000 times;

[0022] Figure 3 This is a microscopic morphology image of the magnetic abrasive prepared in Example 2 of the present invention magnified 2000 times;

[0023] Figure 4 This is a microscopic morphology image of the magnetic abrasive prepared in Example 3 of the present invention magnified 2000 times;

[0024] Figure 5 This is a microscopic morphology image of the magnetic abrasive prepared in Comparative Example 1 of the present invention magnified 2000 times;

[0025] Figure 6 Magnetic hysteresis loops of the magnetic abrasives prepared in Examples 1 to 3 of the present invention and Comparative Example 1;

[0026] Figure 7The roughness curves of the zirconium alloy tube wall before and after processing using the magnetic abrasives prepared in Example 1 and Comparative Example 1 of the present invention, wherein (a) is the roughness curve of the zirconium alloy tube wall before processing, (b) is the roughness curve of the zirconium alloy tube wall after processing using the magnetic abrasive of Comparative Example 1, and (c) is the roughness curve of the zirconium alloy tube wall after processing using the magnetic abrasive of Example 1. DETAILED DESCRIPTION

[0027] All raw materials of the present invention have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0028] There is no particular restriction on the purity of all raw materials in the present invention, and industrial pure raw materials are preferably used in the present invention.

[0029] The invention provides a core-shell structured magnetic abrasive, comprising a ferromagnetic core and a shell coated on the surface of the ferromagnetic core; the shell comprises a transition bonding layer and a hard phase embedded on the surface of the transition bonding layer, and the transition bonding layer comprises a coating layer formed by nano iron powder and an interface diffusion layer between interfaces.

[0030] The core-shell structure magnetic abrasive provided by the present invention comprises a ferromagnetic core. In the present invention, the ferromagnetic core preferably comprises one or more of pure Fe, FeSi or FeNi. As an embodiment of the present invention, the ferromagnet may be Fe-6.5Si with a particle size of 50 to 80 μm. The ferromagnet has excellent oxidation resistance, corrosion resistance and magnetic properties, which is conducive to improving the life of the magnetic abrasive.

[0031] The core-shell structure magnetic abrasive provided by the present invention also includes a shell coated on the surface of the ferromagnetic core. In the present invention, the mass ratio of the ferromagnetic core to the shell is preferably (1-2.5):1. The present invention provides the magnetic abrasive with a regular morphology and size through the setting of the core-shell structure, avoiding irregular morphology and uncontrollable particle size caused by post-processing.

[0032] In the present invention, the shell includes a transition bonding layer and a hard phase embedded in the surface of the transition bonding layer. The present invention embeds the hard phase in the transition bonding layer to solve the problem that the hard phase is difficult to be evenly distributed on the surface of the ferromagnetic core, forms a prominent and obvious grinding layer, improves the relative magnetic permeability of the magnetic abrasive, and has a relatively consistent cutting depth during processing, and has a higher processing efficiency.

[0033] In the present invention, the transition bonding layer includes a coating layer formed by nano iron powder and an interface diffusion layer between interfaces. Nano iron powder has a high saturation magnetization and excellent plasticity. In the present invention, as a transition bonding layer, it can not only be firmly combined with the ferromagnetic body, but also can connect the hard phase through metallurgical bonding, thereby improving the bonding force between the hard phase and the ferromagnetic core; in addition, there are interface diffusion layers between the nano iron powder and the hard phase, and between the nano iron powder and the ferromagnetic core, further improving the bonding force between the ferromagnetic core and the hard phase.

[0034] In the present invention, the interface diffusion layer preferably includes a Fe-Si or Fe-Al layer. The present invention improves the interface bonding force between the ferromagnetic core and the hard phase through the interface diffusion layer, establishes a magnetic channel between the interfaces, weakens the magnetic dilution effect of the hard phase, and improves the magnetic properties of the magnetic abrasive.

[0035] In the present invention, the hard phase preferably includes corundum or silicon carbide. As an embodiment of the present invention, the hard phase can be SiC particles or Al2O3 particles with a particle size of 5 to 20 nm. The hard phase particles have good structural stability, which is conducive to improving the life of the magnetic abrasive.

[0036] The core-shell structure magnetic abrasive provided by the present invention has a regular morphology and size by setting the core-shell structure, thereby avoiding irregular morphology and uncontrollable particle size caused by later processing; by setting a transition bonding layer on the surface of the ferromagnetic core, the hard phase is evenly distributed on the surface of the ferromagnetic body, thereby avoiding the problem of uneven distribution of the hard phase; the transition bonding layer and the hard phase are connected by metallurgical bonding, which not only tightly connects the ferromagnetic body and the hard phase together, but also forms an intermetallic compound interface diffusion layer, establishes a magnetic channel, weakens the magnetic dilution effect of the hard phase, and significantly enhances the magnetic properties of the magnetic abrasive.

[0037] The present invention also provides a method for preparing the core-shell structure magnetic abrasive described in the above technical solution, comprising the following steps:

[0038] 1) mixing nano iron powder and ferromagnetic material and then performing a first ball milling to obtain a first composite powder; the mass content of the nano iron powder in the first composite powder is 15-25%;

[0039] 2) subjecting the first composite powder obtained in step 1) to a second ball milling with a hard phase to obtain a second composite powder, and sintering the second composite powder to obtain a magnetic abrasive; the mass content of the hard phase in the second composite powder is 15-30%; the sintering is carried out in an inert atmosphere at a sintering temperature of 800-1200°C.

[0040] The present invention mixes nano iron powder and bulk magnet and then performs first ball milling to obtain first composite powder.

[0041] In the present invention, the particle size of the nano iron powder is preferably 30-80 nm, more preferably 50-60 nm; as an embodiment of the present invention, the particle size of the nano iron powder can be 35 nm, 40 nm, 45 nm, 55 nm, 65 nm or 70 nm. The particle size of the nano iron powder within the above range is conducive to the uniform coating of the ferromagnetic body by the nano iron powder.

[0042] In the present invention, the particle size of the ferromagnetic body is preferably 50-80 μm, more preferably 60-70 μm; as an embodiment of the present invention, the particle size of the nano iron powder can be 55 μm, 60 μm, 65 μm, 70 μm or 75 μm. The particle size of the ferromagnetic body within the above range is conducive to the uniform coating of the ferromagnetic body by the nano iron powder.

[0043] In the present invention, the mass content of the nano iron powder in the first composite powder is 15-25%, preferably 18-22%; as an embodiment of the present invention, the mass content of the nano iron powder in the first composite powder can be 16%, 17%, 19%, 20%, 21%, 23% or 24%. The present invention limits the amount of the nano iron powder and the ferromagnetic body to the above range, so that the nano iron powder can evenly coat the ferromagnetic body.

[0044] The present invention has no particular requirements for the specific mixing method, and a conventional mixing method in the art can be used. As an embodiment of the present invention, the mixing can be performed in a V-type mixer, and the mixing time can be 30 to 60 minutes.

[0045] In the present invention, the ball-to-material ratio of the first ball milling is preferably (10-15):1, more preferably (12-14):1; as an embodiment of the present invention, the ball-to-material ratio can be 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1. The ball-to-material ratio of the first ball milling is within the above range, which is conducive to uniform coating of the iron powder on the surface of the ferromagnetic body.

[0046] In the present invention, the rotation speed of the first ball mill is preferably 150-250 rpm, more preferably 180-200 rpm; as an embodiment of the present invention, the rotation speed of the first ball mill can be 160 rpm, 170 rpm, 190 rpm, 210 rpm, 220 rpm, 230 rpm or 240 rpm. The rotation speed of the first ball mill within the above range is conducive to uniform coating of the iron powder on the surface of the ferromagnetic body.

[0047] In the present invention, the milling time of the first ball mill is preferably 6 to 8 hours, more preferably 6.5 to 7.5 hours; as an embodiment of the present invention, the milling time of the first ball mill can be 6 hours, 6.5 hours, 7 hours, 7.5 hours or 8 hours. The milling time of the first ball mill within the above range is conducive to uniform coating of the iron powder on the surface of the ferromagnetic body.

[0048] The present invention has no special requirements for the first ball milling device, and a conventional ball milling device in the art can be used. In an embodiment of the present invention, a planetary ball mill is used for the first ball milling, and the grinding beads are alumina grinding beads.

[0049] After obtaining the first composite powder, the present invention performs a second ball milling on the first composite powder and the hard phase to obtain a second composite powder.

[0050] In the present invention, the particle size of the hard phase is preferably 5 to 20 μm, more preferably 10 to 15 μm; as an embodiment of the present invention, the particle size of the hard phase can be 6 μm, 8 μm, 11 μm, 12 μm or 14 μm. The particle size of the hard phase within the above range is conducive to the hard phase being evenly distributed on the surface of the ferromagnetic body; and the particle size of the hard phase within the above range has a better grinding effect of the magnetic abrasive, which is suitable for the precision machining of the surface of complex workpieces.

[0051] In the present invention, the mass content of the hard phase in the second composite powder is 15-30%, preferably 20-25%; as an embodiment of the present invention, the mass content of the hard phase in the second composite powder can be 16%, 18%, 19%, 21%, 22%, 23%, 24%, 26%, 27% or 28%. The present invention limits the amount of the hard phase to the first composite powder within the above range, so that the hard phase can be evenly distributed on the ferromagnetic body.

[0052] In the present invention, the parameters of the second ball mill are the same as those of the first ball mill, and will not be described in detail herein.

[0053] After obtaining the second composite powder, the present invention sintered the second composite powder to obtain magnetic abrasive.

[0054] In the present invention, the sintering is performed in an inert atmosphere. The present invention has no particular limitation on the specific type of the inert gas, and any inert gas commonly used in the art may be used. In an embodiment of the present invention, the sintering is performed in an argon atmosphere. Sintering in an inert atmosphere can prevent oxidation of the magnetic abrasive and reduce magnetic properties.

[0055] In the present invention, the sintering temperature is 800-1200°C, preferably 900-1100°C; as an embodiment of the present invention, the sintering temperature can be 830°C, 860°C, 910°C, 950°C, 1000°C, 1050°C or 1150°C. When the sintering temperature is within the above range, the ferromagnetic body and the hard phase can react with each other through the nano iron powder, and form an interface diffusion layer, thereby improving the bonding force between the hard phase and the ferromagnetic body, establishing a magnetic channel, and weakening the magnetic dilution effect of the hard phase.

[0056] In the present invention, the sintering holding time is preferably 4 to 6 hours, more preferably 4.5 to 5.5 hours; as an embodiment of the present invention, the sintering holding time can be 4.2 hours, 4.4 hours, 4.6 hours, 4.8 hours, 5.0 hours, 5.4 hours or 5.8 hours. The sintering holding time within the above range is conducive to further improving the bonding force between the hard phase and the ferromagnetic body.

[0057] In the present invention, the heating rate of the sintering is preferably 30-50°C / min, more preferably 35-45°C / min; as an embodiment of the present invention, the heating rate of the sintering can be 33°C / min, 36°C / min, 38°C / min, 40°C / min, 43°C / min, 46°C / min or 48°C / min. The heating rate of the sintering within the above range is conducive to further improving the bonding force between the hard phase and the ferromagnetic body.

[0058] The present invention has no special requirements for the sintering device, and a sintering device commonly used in the art can be used. In an embodiment of the present invention, the sintering is performed in a vacuum sintering furnace.

[0059] The present invention coats the surface of a ferromagnet with nano iron powder by ball milling to improve the fragile property of the ferromagnet during processing; then, the hard phase is evenly distributed in the nano iron powder layer by ball milling; the hard phase and the nano iron powder are metallurgically bonded by sintering, and an interface diffusion layer is formed between the nano iron powder layer and the ferromagnet, thereby establishing a magnetic channel and weakening the magnetic dilution effect of the hard phase.

[0060] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0061] Example 1

[0062] A core-shell structure magnetic abrasive, the preparation method schematic diagram is as follows Figure 1 , the specific steps are:

[0063] First, a precision electronic balance is used to weigh 20 g of a composite powder composed of Fe-6.5Si powder and nano-iron powder, wherein the content of nano-iron powder is 20wt%, the particle size of Fe-6.5Si powder is 60μm, and the particle size of nano-iron powder is 50nm; the mixture is mechanically mixed in a V-type mixer for 30 minutes, and then the composite powder is placed in a ball mill in a planetary ball mill for the first ball milling, the ball milling time is 6h, the ball milling speed is 200rpm, and the mass ratio of the composite powder to the alumina grinding beads is 1:10, to obtain a first composite powder.

[0064] A precision electronic balance is used to weigh 20 g of a composite powder composed of a first composite powder and a SiC powder, wherein the SiC powder content is 25 wt % and the SiC particle size is 10 μm; the composite powder is placed in a ball mill for a second ball milling to obtain a second composite powder, the ball milling time is 7 hours, the ball milling speed is 200 rpm, and the ball-to-material ratio is 10:1; the obtained second composite powder is placed in a crucible and placed in a vacuum sintering furnace for high-temperature sintering, the sintering atmosphere is argon, the heating rate is 50°C / min, the temperature is raised to 1000°C, the temperature is kept for 4 hours, and then the furnace is cooled to obtain a magnetic abrasive with a core-shell structure.

[0065] The microstructure of magnetic abrasive was observed using scanning electron microscopy. Figure 2 As shown. Figure 2 It can be seen that the magnetic abrasive is in a regular spherical shape, and the hard phase is evenly distributed on the surface of the ferromagnetic body. Compared with traditional magnetic abrasives, it has better rolling properties.

[0066] Example 2

[0067] A core-shell structure magnetic abrasive, the preparation method is the same as that of Example 1, except that: the content of nano iron powder in the first composite powder is 15wt%, and the first ball milling time is 8h.

[0068] The microstructure of magnetic abrasive was observed using scanning electron microscopy. Figure 3 As shown. Figure 3 It can be seen that the magnetic abrasive is in a regular spherical shape and the hard phase is evenly distributed on the surface of the ferromagnet.

[0069] Example 3

[0070] A core-shell structure magnetic abrasive, the preparation method is the same as that of Example 1, except that: the content of nano iron powder in the first composite powder is 25wt%, and the first ball milling time is 8h.

[0071] The microstructure of magnetic abrasive was observed using scanning electron microscopy. Figure 4 As shown. Figure 4It can be seen that the magnetic abrasive is in a regular spherical shape and the hard phase is evenly distributed on the surface of the ferromagnet.

[0072] Comparative Example 1

[0073] A magnetic abrasive is prepared by the following methods: the particle size of the ferromagnetic phase is 50 μm, the ceramic hard particles are SiC with a particle size of 10 μm, the ferromagnetic phase powder and the hard particle powder are uniformly mixed in a mixer at a mass ratio of 3:1 (wt.%) for 4 hours; 200 g of the mixed powder is taken, 10 g of a phenolic resin binder is added, the mixture is stirred evenly, and then pressed into blocks, which are dried in a vacuum drying oven for 10 hours; a vacuum furnace is used for sintering at a temperature of 1200°C for 3 hours, and the mixture is cooled in the furnace and then mechanically crushed and sieved (100 meshes) for standby use.

[0074] The microstructure of magnetic abrasive was observed using scanning electron microscopy. Figure 5 As shown. Figure 5 It can be seen that the magnetic abrasive is in irregular block shape, with hard phase and ferromagnetic phase distributed alternately.

[0075] Test Example 1

[0076] The magnetic grinding balls prepared in Examples 1 to 3 and Comparative Example 1 were subjected to magnetic testing. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the core-shell structure magnetic grinding ball provided by the present invention has higher magnetic permeability and lower coercive force.

[0077] Test Example 2

[0078] The zirconium alloy tube wall was processed using the magnetic abrasive of Comparative Example 1 and the core-shell structure magnetic abrasive of Example 1, respectively, with a processing time of 10 min and a processing length of 10 mm. The roughness Ra value of the processed surface was measured using a roughness measuring instrument TR200, as shown in FIG. Figure 7 shown.

[0079] Data recorded by the roughness measuring instrument: initial roughness of the zirconium alloy tube wall Ra=0.317±0.01μm, roughness after processing with the magnetic abrasive of Comparative Example 1 Ra=0.212±0.01μm, roughness after processing with the core-shell structure magnetic abrasive of Example 1 Ra=0.185±0.01μm.

[0080] The magnetic abrasives of Example 1 and Comparative Example 1 were continued to be used for processing. The grinding life of the magnetic abrasive of Example 1 was 80 min, and the grinding life of the magnetic abrasive of Comparative Example 1 was 60 min.

[0081] It can be seen from the above embodiments and comparative examples that the core-shell structured magnetic abrasive provided by the present invention is in a regular spherical shape, and the hard phase is evenly distributed on the surface of the ferromagnetic body. Compared with the magnetic abrasive prepared by the bonding method, it has higher magnetic permeability and lower coercive force, as well as longer service life.

[0082] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A core-shell structure magnetic abrasive, comprising a ferromagnetic core and a shell coated on the surface of the ferromagnetic core; the shell comprises a transition bonding layer and a hard phase embedded on the surface of the transition bonding layer, the transition bonding layer comprises a coating layer formed by nano iron powder and an interface diffusion layer between interfaces.

2. The magnetic abrasive according to claim 1, characterized in that: The ferromagnetic core includes one or more of pure Fe, FeSi or FeNi.

3. The magnetic abrasive according to claim 1 or 2, characterized in that: The hard phase includes corundum or silicon carbide.

4. The magnetic abrasive according to claim 3, characterized in that: The interface diffusion layer includes a Fe-Si or Fe-Al layer.

5. The method for preparing the core-shell structure magnetic abrasive according to any one of claims 1 to 4, characterized in that: The steps include: 1) mixing nano iron powder and ferromagnetic material and then performing a first ball milling to obtain a first composite powder; the mass content of the nano iron powder in the first composite powder is 15-25%; 2) subjecting the first composite powder obtained in step 1) to a second ball milling with a hard phase to obtain a second composite powder, and sintering the second composite powder to obtain a magnetic abrasive; the mass content of the hard phase in the second composite powder is 15-30%; the sintering is carried out in an inert atmosphere at a sintering temperature of 800-1200°C.

6. The preparation method according to claim 5, characterized in that: In the step 1), the particle size of the ferromagnetic material is 50 to 80 μm, and the particle size of the nano iron powder is 30 to 80 nm.

7. The preparation method according to claim 5 or 6, characterized in that: The ball-to-material ratio of the first ball mill in step 1) is (10-15):1, the rotation speed is 150-250 rpm, and the ball milling time is 6-8 hours.

8. The preparation method according to claim 5, characterized in that: The particle size of the hard phase in step 2) is 5 to 20 μm.

9. The preparation method according to claim 5 or 8, characterized in that: The ball-to-material ratio of the second ball mill in step 2) is (10-15):1, the rotation speed is 150-250 rpm, and the ball milling time is 6-8 hours.

10. The preparation method according to claim 5, characterized in that: The heating rate of sintering in step 2) is 30-50°C / min.

Citation Information

Patent Citations

  • Normal atmosphere sintering method for magnetic grinding medium

    CN101481597A

  • Spherical magnetic abrasive and preparation method thereof

    CN112280535A

  • METHOD FOR PRODUCING Fe-Si BASED SOFT MAGNETISM SINTERED ALLOY HAVING HIGH DENSITY AND HIGH PERMEABILITY

    JP2004014614A

  • Magnetic abrasive powder and method manufacturing the same

    KR1020100136807A

  • Core-Shell Structured Composite Powder Electromagnetic Wave Absorber Formed by Coating Fe-Based Nanocrystalline Alloy with Carbon, and Preparation Method Thereof

    US20220380609A1

Cited By

  • Diamond-iron-based magnetic composite abrasive and preparation method thereof

    CN120637077A

  • Diamond-iron-based magnetic composite abrasive and preparation method thereof

    CN120637077B